2015
DOI: 10.1063/1.4921810
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyrimidine and water as underlying molecular constituents for describing radiation damage in living tissue: A comparative study

Abstract: Water is often used as the medium for characterizing the effects of radiation on living tissue. However, in this study, charged-particle track simulations are employed to quantify the induced physicochemical and potential biological implications when a primary ionising particle with energy 10 keV strikes a medium made up entirely of water or pyrimidine. Note that pyrimidine was chosen as the DNA/RNA bases cytosine, thymine, and uracil can be considered pyrimidine derivatives. This study aims to assess the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Chiari et al 9 There are several studies reported fore + -N 2 scatteringin the literature [12][13][14][15][16][17][18][19][20][21][22][23] . Similarly for O 2 , there exist previous experimental results from Marler et al 5 , Katayama et al 24 and Dababneh et al 25 and theoretical results from De-Heng et al 26 and Raj 27 . Thus, it is quite evident that N2and…”
Section: Introductionmentioning
confidence: 70%
“…Chiari et al 9 There are several studies reported fore + -N 2 scatteringin the literature [12][13][14][15][16][17][18][19][20][21][22][23] . Similarly for O 2 , there exist previous experimental results from Marler et al 5 , Katayama et al 24 and Dababneh et al 25 and theoretical results from De-Heng et al 26 and Raj 27 . Thus, it is quite evident that N2and…”
Section: Introductionmentioning
confidence: 70%
“…[4][5][6][7][8] The present submission is a new step in this series of investigations with furfural, and as it is the integral cross sections (ICSs) that are generally of most interest to the modelling communities [9][10][11][12][13][14] it therefore represents an important achievement. Note that this follows on from a similarly extensive study on phenol, [15][16][17][18][19][20] another important by-product from the application of atmosphericpressure plasmas to biomass.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] The present submission is a new step in this series of investigations with furfural, and as it is the integral cross sections (ICSs) that are generally of most interest to the modelling communities [9][10][11][12][13][14] it therefore represents an important achievement. Note that this follows on from a similarly extensive study on phenol, [15][16][17][18][19][20] another important by-product from the application of atmosphericpressure plasmas to biomass.…”
Section: Introductionmentioning
confidence: 99%